A STUDY ON THE CORE CURRICULUM OF ACCOUNTING AS THE COMPETENCIES BUILDER OF THE ACCOUNTING GRADUATES (A Study on The Accounting Graduates Who Work at Private Companies, State Companies, Non-Profit Organizations, And Public Accountant Firms in Surabaya) - Diana Zuhroh; Parawiyati Parawiyati; Eni Lisetyati (Faculty of Economics and Business, Universitas Gadjah Mada, 2009)
As generally known accounting graduates are considered to have low quality. Based on recent studies and practitioners experience, there are two reasons for this: (1) accounting curriculums are not matched with up to date practices, and (2) they were not introducedto real practices that they will face when they have finished their study. The objective of this study are (1) to obtain an empirical evidence about accounting practitioner competences, and (2) establishing a curriculum structure that is relevant with user needs.The study used and are sent questionnaire to two hundreds respondents (accounting practioners) in Surabaya. They asked to rate on one to five point Likert type scale the importance of accounting competents (in knowledge, skills, and ethics), and the importance of subjects needed in developing these competencies as well. The subjects listed based on goverment regulation No. 232/U/2000 and UU No. 045/U/2002. The scale is set low importance to one and high importance to five rating.This paper reports competencies and subjects listed on detail ranked in order of mean score. Competences and subjects with higher rank are needed in today practice. The Accounting Department is suggested to use this result in designing its curriculum for reducing gap between practice and education and to improve accounting graduates’ quality.Keywords : Competency, Curriculum , Accounting Education, Accounting Graduates.